2017
DOI: 10.1016/j.eurpsy.2017.01.711
|View full text |Cite
|
Sign up to set email alerts
|

Depression among elderly cancer patients

Abstract: IntroductionDepression is one of the most common mental illnesses in the elderly and its consequences are severe.AimsTo measure the prevalence of depression in elderly cancer patients and subsequently determine the sociodemographic and clinical factors correlated with this disorder.MethodsWe conducted a descriptive and analytical cross-sectional study of patients aged over than 65 years old, suffering from cancer and who had no cognitive impairment, admitted in 2013 in the Oncology and palliative care unit of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
1
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
3
1
1
Order By: Relevance
“…In the present study, the widowed elder patients had the highest depression score, which agrees with the results reported by Ghanmi et al [30] It seems that living with the family is associated with a greater participation in social activities and a higher self-esteem.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, the widowed elder patients had the highest depression score, which agrees with the results reported by Ghanmi et al [30] It seems that living with the family is associated with a greater participation in social activities and a higher self-esteem.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the individuals with chronic diseases had higher depression scores, and depression had a significant relationship with diabetes and respiratory diseases, which concur with the results reported by Ghanmi et al and Weiss Wiesel et al [530] In Nikbakht et al study, depression was significantly higher in patients with chronic diseases. [11] Physical disorders and their related symptoms have a direct effect on mental health.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Pain was found to be significantly associated with depression, and as severity of pain increased the risk of having depression also increased among the current study participants. This finding is consistent with reports from studies conducted in Taiwan, Tunisia and Ethiopia [36, 43, 45]. This suggests that pain management is very crucial for breast cancer patients in the prevention of depression and other psychological co-morbidities.…”
Section: Discussionsupporting
confidence: 92%
“…Similar prevalence of depression was reported from studies conducted in Malaysia (22%), Iraq (24.7%), Iran (26.7%), Qatar (27.7%), India (28%) and Morocco (26.9%) [10,[31][32][33][34][35]. However, our finding is lower than a study conducted in Tunisia which reported the prevalence of depression among cancer patients to be 48%, the explanation for such big difference could be the inclusion of women only aged 65 and above, who are demographically at higher risk of depression [36]. Similarly, high prevalence of depression was reported from Turkey (46%) [37], South Africa (36.6%) [38], Mexico (43%) [39] and Nigeria 40.3% [28] using Hospital Anxiety and Depression (HADs) tool, Center for Epidemiologic Studies Depression Scale (CESD) and Mini International Neuropsychiatric Interview (MINI) for assessment of depression respectively.…”
Section: Discussioncontrasting
confidence: 74%